The impact of the COVID-19 pandemic on education in Bangladesh and its mitigation - Kamrujjaman, Md.; Sinje, Sadia Shihab; Nandi, Tanni Rani; Islam, Fariha; Rahman, Md. Atikur; Akhi, Asma Akter; Alam, Md. Shah (Fırat Evirgen, 2024)
The global COVID-19 pandemic disrupted various facets of societal functioning, with the education sector facing unprecedented challenges. The sudden closure of schools and universities, coupled with the shift towards remote learning, created a dynamic educational environment. It significantly affected academic performance, psychological health, dropout rates, school closures, and even increased early marriage rates in Bangladesh. In 2021, the dropout rate stood at 14.15 percent. This study delves into the specific repercussions of the pandemic on the education landscape in Bangladesh. The research reveals the disparities in access to online education, shedding light on the socio-economic factors influencing digital learning engagement. Through a comprehensive analysis of quantitative and qualitative data, we explore the multifaceted effects on educational institutions, students, and educators. We present the impact of COVID-19 on education graphically using interpolation polynomials. Mitigating the impact of COVID-19 on the education sector in Bangladesh necessitates a multifaceted approach that addresses various interconnected challenges. Moreover, prioritizing mental health support for students, teachers, and parents is paramount in navigating the emotional toll of the pandemic. Collaboration and partnerships with international organizations, non-government organizations (NGOs), and private sector entities are indispensable for mobilizing resources and expertise. Bangladesh can effectively manage the pandemic's complications and ensure the continued viability of its educational system by implementing such an all-encompassing approach.
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)